Một số thiết bị và kỹ thuật phổ hiện đại sử dụng trong phân tích phát hiện thuốc giả tại hiện trường và trong phòng thí nghiệm / Trần Việt Hùng - Trần, Việt Hùng
The following mordern spectral equipments and techniques of rapid analysis and detection of counterfeiting for field or/and laboratory practice are introduced: Handheld Near Infrared (NIR), handheld Raman, X-ray Diffraction ( XRD), Mass Spectrometry (MS), Nuclear Magnetic Resonance (NMR).